ECG Signal Classification Technique Based on Deep Features Using Differential Evolution Algorithm Extreme Learning Machine (DEA-ELM) - Dıker, Aykut; Avci, Engin (My University, 2020)
The movements of electrocardiogram (ECG) signals are very important in the diagnosis of heart disorders.Machine learning methods are widely used to classify ECG signals. The aim of this work is to contribute to theclassification of ECG signals using the Differential Evolution Algorithm Extreme Learning Machine (DGA-ELM).In this paper, a public heart records in Physionet was utilized to classify ECG signals. The pre-processing wasapplied to eliminate the ECG signals from noise. Then, the ECG signals were converted to spectrograms for thefeature extraction stage. A method was used originated on Convolutional Neural Network (CNN) to obtain theattributes of ECG signals. The DGA-ELM algorithm was used to select the best activation function. In this context,the best cost value 79.37% with a sigmoid activation function and 750 iteration in the classification made withDGA-ELM was achieved.
Keywords: Bilgisayar Bilimleri; Yazılım Mühendisliği; Kalp ve Kalp Damar Sistemi